Kekerasan seksual UPAYA DPPKBP3A DALAM MENANGANI KEKERASAN SEKSUAL DI KOTA TASIKMALAYA: UPAYA DPPKBP3A DALAM MENANGANI KEKERASAN SEKSUAL DI KOTA TASIKMALAYA - Edi, Lutfia Nisa (JPUS: Jurnal Pendidikan Untuk Semua, 2023)
The case of getting pregnant out of wedlock is no longer a shame to cover up, the absence of barriers in association makes the level of violence in Indonesia carried out arbitrarily and it is easy to be targeted as the next victim. The aim of the study was to find out the efforts of the DPPKBP3A in dealing with sexual violence in the City of Tasikmalaya. The research method used is a descriptive method with an approach qualitative. Data collection techniques used are interview techniques, observation, and documentation studies. The results of the research we did, DPPKBP3A have made efforts to handle cases of sexual violence, especially in the City of Tasikmalaya. In handling it, DPPKBP3A has carried out programs to deal with cases of sexual violence, one of which is the Socialization Program on the Prevention of Violence against Women and Children in the Community.